THE JURIDICAL ANALYSIS OF LEGAL NORMS RELATED TO BPJS REFERRALS IN PUSKESMAS TO GOVERNMENT HOSPITALS - Kurniadi, Adji Bhayu Kurniadi; Huda, Mohkhamad Khoirul (Penerbit Universitas Atma Jaya Yogyakarta, 2024)
The Regent's instructions to the Head of the Health Service in city M with letter number 445/ /402.102/2021 regarding BPJS Health Center patients if referred are directed to the Regional Government Hospital. This instruction creates a conflict between legal norms and applicable government regulations and Health BPJS regulations. Because it can have an impact on tiered referral services in hospitals. In the Regulation of the Minister of Health of the Republic of Indonesia Number 01 of 2012 it is explained that referrals are made in stages, according to medical needs starting from the first level of health services. Social health insurance is a right for residents regulated in RI Law No. 40 of 2004 and Regulation of the Minister of Health of the Republic of Indonesia Number 71 of 2013 concerning Health Services. State that follow-up referrals are individual health services that are specialist and sub-specialist. The purpose of this study is to analyze the impact that will occur if the implementation of the Regent's instructions regarding tiered referrals in City M is carried out. The research method used Normative Descriptive Analysis with a statutory regulation approach and analysis using secondary data in the form of Legal Materials with Literature Studies, so that it becomes clear how the correct position is between Government instructions and regulations and the applicable Health BPJS.